Synthesis and rotational dynamics of diazamacrocycles having bridged 1, 4-naphthylene as framed molecular rotors. Issue 43 (19th October 2022) - Kurimoto, Taichi; Inagaki, Yusuke; Ohara, Kazuaki; Yamaguchi, Kentaro; Setaka, Wataru
Abstract : 1, 4-Naphthylene bridged diazamacrocycles were synthesized and characterized as novel framed molecular rotors, and dependence of the rotation on the frame size was investigated. Abstract : The rotation of a part of a molecule has attracted attention because of its possible role in the development of an artificial molecular rotor. In this study, 1, 4-naphthylene bridged diazamacrocycles, in which the 1, 4-diaminonaphthalene moiety is bridged by two long alkyl chains, were designed as novel framed molecular rotors, and the dependence of the rotation on the frame size were investigated. Framed rotors C n Np ( n = 12, 14, 16, 18), where the number in the compound name indicates the length of a side chain, were synthesized by direct cyclization of 1, 4-naphthalenediamine with α, ω-dihaloalkane in the presence of Na2 CO3 as the base. The rotation of the naphthylene rotor in C12Np, C14Np, and C16Np was nearly suppressed in solution, whereas the rotor in C18Np showed rotation, as confirmed by the temperature-dependent coalescence of the NMR signals of the α-CH2 .